Explanatory Models of Prospective Memory:: A Theoretical Review - Matos, Patrícia (2014)
This article presents a review of the literature concerning the cognitive mechanisms underlying prospectivememory, organized according to the division of the different phases of this phenomenon (i.e., encoding, retention and retrieval).Initially, a variety of research data is presented supporting different explanatory approaches of the phenomenon of intendedactions, namely their automatic and strategic processes. Also some potential explanations are presented about the mechanismsin effect during the retention interval and the encoding phase.